Strengthening Students on Materials for the Rice Cultivation System (Beume) of the Nanga Mahap Village Community in the Covid-19 Pandemic Era - Emi Tipuk Lestari; Melly Sulastri; Saiful Bahri; Sandie; Dewi Risalah (Lectura : Jurnal Pendidikan, 2022)
This study aims to support students on the material of the rice cultivation system (beume) of the Nanga Mahap Village community. The sub-objectives of this research are (1) the material for the cultivation system of the Nanga Mahap Village community, (2) the implementation of the teacher in explaining the material, (3) strengthening students on the material for the rice cultivation system (beume). This research uses a descriptive method. Samples were taken by purposive sampling technique. Data were collected by direct observation, direct communication, and documentation. The analysis used is descriptive qualitative. The results of the research show: (1) The people of Nanga Mahap Village refer to rice farming activities as beuma/beume. This farming tradition is traditional with a slash and burn system and then planting rice. (2) The implementation of the teacher in delivering lecture material and assignments. The assignment is in the form of students doing simple research on the farming system around their environment and inviting students to construct with cultivation in prehistoric times. (3) strengthening the rice cultivation system (beume) in the form of students' understanding of the material which is quite good, which is indicated by the active involvement of students in learning. This material makes students think contextually between the cultivation system of prehistoric times and the farming system (beume).